Effect of Moringa oleifera leaf extract on the physicochemical properties of modified atmosphere packaged raw beef. (March 2015) - Shah, Manzoor Ahmad; Bosco, Sowriappan John Don; Mir, Shabir Ahmad
Highlights: Moringa oleifera leaf extract (MLE) is a good source of phenolic compounds with significant radical scavenging activity and reducing power. Raw beef treated with MLE had a significant ( p < 0.05) effect on the reduction of TBARS values compared with control. MLE had a significant effect on color parameters as compared to control. MLE can be used as a natural antioxidant to prevent lipid oxidation in raw meat, packaged in high oxygen MAP. Abstract: The effect of Moringa oleifera leaf extract (MLE) on the physicochemical properties of raw beef stored in modified atmosphere packaging (MAP) under 12 days of refrigerated temperature was investigated. MLE was prepared using water as solvent and its total phenolic content ranged from 46.13 to 49.45 mg gallic acid equivalent/g of extract. Raw beef chunks were treated with different concentrations of MLE (0.1, 0.2 and 0.3 g MLE/L solution) and BHT (0.2 g BHT/L solution) and compared with control (no antioxidant) and packaged in gas combination of 80% O2 and 20% CO2 . MLE had a significant ( p < 0.05) effect on pH, TBARS and color parameters as compared to control but had non-significant effect on water holding capacity, cooking loss, shear value and microbiological quality of packaged beef. The results indicate that the MLE can be used as natural antioxidant to preserve raw beef packaged in high oxygen MAP.